Nuclear spin-lattice relaxation rate in Kondo superconductors in the gapless state - I. M. Tang (2018)
The host nuclear spin-lattice relaxation rates in Kondo superconductors in the gapless state are derived within the framework of the Matsuura, Ichinose, and Nagaoka (MIN) theory of the Kondo effect. The relaxation rates for both low-TK and high-TK Kondo superconductors are obtained. The temperature dependence of the relaxation rate in low-TK Kondo superconductors in the gapless state arising from the pair breaking by the Kondo impurity is obtained. The dependence of the relaxation rate for high-TK Kondo superconductors in the gapless state on the external magnetic field producing the gapless state is also obtained. © 1985 Plenum Publishing Corporation.